Management Industry of Shuttlecock Sport Equipment in Tegal District - Arini Ayuningtyas; Hermawan Pamot Raharjo; Mugiyo Hartono; Aris Mulyono (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
The purpose of this research is to know how the management function that applied by each shuttlecock craftsman in Lawatan Village. This research uses qualitative methode. The data source for this research are primary and secondary. The primary data is taken by observation and interview, meanwhile the secondry data is taken by documentation. There are four interviewees. The research is condusted in two different shuttlecock companies, they are UD. Tri Sakti and Gramedia. The purpose of the research is to know the management of shuttlecock industry in Lawatan Village. The verification of data validity in this research used credibility test, transferability test, dependability test, and confirmability test. The result of this research found that the management in 2 shuttlecock companies have been applied well. The planning is well planned by each manager of shuttlecock companies. The orginizing from each companies have been stated by the manager with some criterias. The briefing is well performed by each manager, so that the employee is be able to work according to the direction. Then controlling from each company need to be improved to minimilize error in working. The conclution is management of Sport Equipment Industry Shuttlecock in Lawatan Village implements well four management functions, planning, orginizing, briefing, and controlling.